1995
DOI: 10.3109/00016349509024379
|View full text |Cite
|
Sign up to set email alerts
|

Human placental lactogen and pregnancy‐associated plasma protein A in first trimester and subsequent fetal growth

Abstract: Higher levels of human placental lactogen and pregnancy-associated plasma protein A predicted earlier delivery, maybe because of better fetal growth, and higher levels of pregnancy-associated plasma protein A predicted better fetal growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 9 publications
4
30
1
Order By: Relevance
“…Perhaps the best studied of these proteases is pregnancyassociated plasma protein A (PAPP-A), which is a metalloproteinase secreted by the decidua and placenta into maternal circulation where it is able to cleave IGFBP4 and IGFBP5 and thus increase the activity of local IGFs [73][74][75][76][77]. The levels of PAPP-A in maternal circulation during the first trimester have been found to be associated with subsequent fetal growth and birth weight [78][79][80], suggesting that the levels of placental IGFs observed very early in gestation may determine the extent of fetal growth throughout the pregnancy [79]. Low levels of PAPP-A in the first trimester of gestation have been found to be associated with intrauterine growth restriction, stillbirth, and preterm delivery [76].…”
Section: Igf1 and Igf2 Receptorsmentioning
confidence: 98%
“…Perhaps the best studied of these proteases is pregnancyassociated plasma protein A (PAPP-A), which is a metalloproteinase secreted by the decidua and placenta into maternal circulation where it is able to cleave IGFBP4 and IGFBP5 and thus increase the activity of local IGFs [73][74][75][76][77]. The levels of PAPP-A in maternal circulation during the first trimester have been found to be associated with subsequent fetal growth and birth weight [78][79][80], suggesting that the levels of placental IGFs observed very early in gestation may determine the extent of fetal growth throughout the pregnancy [79]. Low levels of PAPP-A in the first trimester of gestation have been found to be associated with intrauterine growth restriction, stillbirth, and preterm delivery [76].…”
Section: Igf1 and Igf2 Receptorsmentioning
confidence: 98%
“…Studies have shown that low free β-HCG and PAPP-A levels in the first trimester are associated with pregnancy complications. 10,11 In particular, low PAPP-A levels are significantly associated with spontaneous fetal loss, low-birth-weight babies, intra-uterine growth restriction, pregnancy-induced hypertension, preeclampsia, preterm rupture of membranes, and placental abruption. [12][13][14] Several studies have shown that women with pre-existing diabetes mellitus (DM) have significantly lower PAPP-A levels than those without DM.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PAPPA is considered as a bioactive IGF-1 promoting enzyme in the IGF system 10 . PAPPA is predominantly produced by embryonic trophoblast cells and the placenta, and its concentration in pregnant women serum is dramatically increased during the first trimester, and is continuously elevated until the end of pregnancy 11 . Notably, low circulating PAPPA levels may indicate a high risk of delivery of a small-for-gestational age infant, Down’s syndrome and preeclampsia 1214 .…”
Section: Introductionmentioning
confidence: 99%